2019
DOI: 10.1080/19475705.2019.1650126
|View full text |Cite
|
Sign up to set email alerts
|

Novel hybrids of adaptive neuro-fuzzy inference system (ANFIS) with several metaheuristic algorithms for spatial susceptibility assessment of seismic-induced landslide

Abstract: Strong ground motions usually trigger lots of slope failures in the affected area. In this work, we analyse the occurrence likelihood of earthquake-triggered landslide by employing the ensembles of adaptive neuro-fuzzy inference systems (ANFIS) with four well-known metaheuristics techniques, namely particle swarm optimization (PSO), genetic algorithm (GA), ant colony optimization (ACO), and differential evolution (DE) algorithms. Twelve landslide conditioning factors namely, elevation, slope degree, lithology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 80 publications
(31 citation statements)
references
References 85 publications
0
21
0
Order By: Relevance
“…Furthermore, many scholars have proven that the incorporation of hybrid metaheuristic algorithms with a regular predictive algorithm can result in computational drawbacks like local minima [24][25][26][27]. Studies such as [28,29] have demonstrated the potential of the ANFIS to be hybridized in order to naturalize hazard modeling, such as landslide and flood hazards. In the field of SSS, different works have explored the use of hybrid models for optimizing typical predictors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many scholars have proven that the incorporation of hybrid metaheuristic algorithms with a regular predictive algorithm can result in computational drawbacks like local minima [24][25][26][27]. Studies such as [28,29] have demonstrated the potential of the ANFIS to be hybridized in order to naturalize hazard modeling, such as landslide and flood hazards. In the field of SSS, different works have explored the use of hybrid models for optimizing typical predictors.…”
Section: Introductionmentioning
confidence: 99%
“…As is known, landslide susceptibility mapping is an essential prerequisite for landslide risk management [5,6]. A proper landslide risk assessment entails determining the effective landslide parameters for discovering the spatial relationship between them and occurred landslides.…”
Section: Introductionmentioning
confidence: 99%
“…The recent advances in metaheuristic science led to the proper optimization of different engineering parameters. Moreover, it was proven that synthesizing these algorithms with typical predictive models led to raising their accuracy through prevailing computational weaknesses [31][32][33]. In the field of shear strength analysis, well-known optimization algorithms such as the cuckoo search optimization (CSO), particle swarm optimization (PSO), and genetic algorithm (GA) were applied for the performance improvement of intelligent approaches of least-squares SVM, support vector regression (SVR), and adaptive neuro-fuzzy inference system (ANFIS) [6,34,35].…”
Section: Introductionmentioning
confidence: 99%